Modeling the Antecedents and Outcomes of Knowledge Stagnation in the Ministry of Health, Treatment, and Medical Education - Parmouzeh, Abdol Alim; Beheshtifar, Malikeh; Ziaaddini, Mohamad (Future of Work and Digital Management Journal, 2024)
This study aimed to develop a multi-level interpretive structural model identifying the antecedents and outcomes of knowledge stagnation in the Ministry of Health, Treatment, and Medical Education. This research employed a mixed-method exploratory–confirmatory design, integrating qualitative analysis, fuzzy Delphi validation, and Interpretive Structural Modeling (ISM). In the qualitative phase, 20 experts—including faculty members and senior specialists in organizational behavior, human resource management, and administrative roles within the Ministry—were selected through purposive sampling until theoretical saturation. Semi-structured interviews were conducted to extract initial antecedents and outcomes of knowledge stagnation. The extracted factors were then evaluated by 44 additional experts using a fuzzy Delphi questionnaire to determine relevance, clarity, and appropriateness. Linguistic judgments were converted into triangular fuzzy numbers and defuzzified using Minkowski-based formulas to establish consensus. In the final phase, ISM was applied to model hierarchical relationships among confirmed antecedents and outcomes across structural, behavioral, and contextual dimensions, generating driving and dependence powers for each factor and determining multi-level structures. The ISM results revealed that structural weaknesses—including inadequate infrastructures, inappropriate hierarchical structures, and insufficient work processes—serve as the strongest antecedents driving knowledge stagnation. Behavioral determinants such as weak knowledge leadership, poor communication networks, lack of knowledge absorption, and resistance to change emerged as core behavioral drivers. Contextual factors, particularly weak national regulations and lack of cross-ministerial knowledge modeling, showed significant systemic influence. The outcomes hierarchy indicated that threatened organizational survival, diminished agility, reduced learning, loss of innovation, and declining societal knowledge quality are key consequences. The multi-level model demonstrated that foundational structural and contextual weaknesses cascade into behavioral stagnation and ultimately shape strategic and societal outcomes. Knowledge stagnation in the Ministry of Health arises from interconnected structural, behavioral, and contextual deficiencies that reinforce one another, and addressing it requires systemic interventions that strengthen infrastructures, leadership, learning culture, and inter-organizational knowledge governance.